Computed tomographic evaluation of the canine intercondylar notch in normal and cruciate deficient stifles - Lewis, B. A.; Allen, D. A.; Henrikson, T. D.; Lehenbauer, T. W. (Veterinary and Comparative Orthopaedics and Traumatology, 2008)
In the human and veterinary orthopaedic literature it has been implied that intercondylar notch stenosis is a mechanical factor in cranial cruciate ligament rupture and intraarticular graft failure. The patients in this study were classified as normal (32), unilateral cruciate rupture (23), or bilateral cruciate rupture (17). The dogs were placed under general anaesthesia and both stifles were scanned via computed tomography (CT) as previously described. Three CT slices at predetermined levels were evaluated within the notch. Measurements included opening notch angle, notch width and height, condyle width, and notch width index (notch width/ condyle width) at two different heights within the notch. Intercondylar notch measurements at the most cranial extent were significantly more narrow in unilateral and bilaterally affected stifles when compared to the normal population. Significant differences were noted in the opening notch angle (ONA), notch width index (NWI), NWI at two thirds notch height (NWI2/3), and tibial slope index (TSI). No significant differences were noted between unilateral and bilateral affected stifles. Increased mechanical contact of the cranial cruciate ligament with a stenotic intercondylar notch may predispose the ligament to mechanical wear and structural weakening. Intercondylar notch measurements have been used as a tool to predict the risk of anterior cruciate ligament injury in young human athletes, and to assess the risk factors for intra-articular graft replacements. Our findings may be useful in developing similar predictive models using stifle CT scans.
Keywords: Intercondylar notch; computed tomography; cruciate ligament; canine